Full-hexacyanometallate aqueous redox flow batteries exceeding 1.5 V in an aqueous solution - Jang, Ji-Eun (2024)
Aqueous redox flow batteries (RFBs) have attracted significant attention as energy storage systems by virtue of their inexpensive nature and long-lasting features. Although all-vanadium RFBs exhibit long lifetimes, the cost of vanadium resources fluctuates considerably, and is generally expensive. Iron–chromium RFBs take advantage of utilizing a low-cost and large abundance of iron and chromite ore; however, the redox chemistry of CrII/III generally involves strong Jahn–Teller effects. Herein, this work introduces a new Cr-based negolyte coordinated with strong-field ligands capable of mitigating strong Jahn–Teller effects, thereby facilitating low redox potential, high stability, and rapid kinetics. The balanced full-cell configuration features a stable lifetime of 500 cycles with energy density of 14 Wh L−1. With an excessive posolyte, the full-cell can attain a high energy density of 38.6 Wh L−1 as a single electron redox process. Consequently, the proposed system opens new avenues for the development of high-performance RFBs.